Implementation of Higher Order Thinking Skills (HOTS) Based on Character Building Education at Nurul Jadid Senior High School Paiton, Probolinggo - Muzammil; Riduwan Hamimi (Universitas Yudharta Pasuruan, 2021)
AbstractThe nation's agenda towards Indonesia Gold in 2045 becomes a severe challenge for the world of education in Indonesia, because education as the main motor is required to improve itself to prepare the nation's generation that is resilient, critical, adaptive and competitive in accordance with the demands and needs of the times in its time. School as the main home of the education process must compete in printing a generation of achievers and characters. This research aims to discuss a) Implementation of HOTS based character education at Nurul Jadid High School and b) The concept of HOTS in the Formation of Character Education in Nurul Jadid High School. The research method used in this research is Case Study Research with a qualitative approach. The method of data analysis in this study is narrative analysis. The results of this study found that the application of HOTS at Nurul Jadid High School uses four learning models, namely problem-based learning, inquiry-based learning, discovery learning and project-based learning to foster character in students. The use of transformative learning education model in Islamic boarding school is also one of the goals to create a dialogueal, humanist, and communicative teaching-learning activity in developing the psychiatric intelligence of students (Intellectual Quotation, Emotional Quotation, and Spiritual Quotation).